The practice, nature, and impact of nurse-led type 2 diabetic foot prevention services and educational programs in Sub-Saharan Africa: a scoping review - Rincy Sajith; Louise Ackers; Simona Ackers-Johnson; Daniel J. Parker; Melanie Stephens (Frontiers Media S.A., 2024)
ObjectiveThe objective of this study is to assess the scope of existing practice, nature, and impact of nurse-led type 2 diabetic foot prevention services and educational programmes in Sub-Saharan Africa (SSA).IntroductionType 2 diabetes mellitus (T2DM) in SSA imposes a heavy burden on current healthcare services. Complications such as foot ulcers can have a significant impact on patient care and healthcare resources. It is imperative to identify patients at risk of developing diabetic foot complications and empower them with diabetes self-management education and support from specialised foot clinics is crucial. However, the availability of such programmes and services in SSA is limited.Inclusion criteriaStudies of nurse-led diabetic foot prevention services and/or educational programmes in low- or middle-income countries in SSA for adults with T2DM, written in English, between August 2013 and March 2024 were considered.MethodsFollowing the standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for conducting and reporting scoping reviews, searches were conducted on four electronic databases (CINAHL, ProQuest, MEDLINE, and Scopus) and Google Scholar. The titles and abstracts were scrutinised. All eligible papers were retrieved and screened for full text.ResultsThe review included ten studies (across 14 papers), all of which focused on nurse-led diabetes self-management education (DSME) programmes in SSA. There are no specific educational programmes or services led by nurses that focus exclusively on diabetic foot prevention. The analysis highlighted the components of successful nurse-led DSMEs that led to positive glycaemic control and self-care behaviors, including the focus on behavior change and the DSME should be co-produced with service users. The theoretical aspects of the DSME include evidence-based, structured, interactive, culturally and linguistically appropriate group-based activities. The DSME should be delivered over a period of several weeks, and sessions should last between 1.5 and 2 h. Barriers to delivery and participation include the rainy season, stockouts, time and resources needed, and a DSME that meets diverse levels of literacy and education.ConclusionThere is a heightened need for nurse-led, co-produced, culturally congruent, frugal, and sustainable education interventions or programmes. There is also a need for diabetic foot screening and foot ulcer prevention services that can operate sustainably alongside these educational interventions through task-shifted, simple, and frugal initiatives.